2021
DOI: 10.9734/jammr/2021/v33i1530988
|View full text |Cite
|
Sign up to set email alerts
|

Antibiogram of Methicillin Resistant Staphyloccocus aureus solated from Nasal Carriage of Some University Students of Rivers State University, Port Harcourt, Nigeria

Abstract: Staphylococcus aureus is ubiquitous, and highly adaptive pathogen that colonizes the skin and mucous membrane of the anterior nares, MRSA most often causes skin infections. In some cases, it causes pneumonia (lung infection) and other infections. If left untreated, MRSA infections can become severe and cause sepsis—the body's extreme response to an infection.Therefore, this study was aimed to evaluate the antibiogram of Methicillin ResistantStaphylococcus aureus from nasal carriage of Students in Rivers State … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Qquestionnaires designed with both open-ended questions such as age and closed ended questions with nominal categorical values such as gender were administered. Data including age, gender and symptoms were also collected [4].…”
Section: Sample Collectionmentioning
confidence: 99%
See 3 more Smart Citations
“…Qquestionnaires designed with both open-ended questions such as age and closed ended questions with nominal categorical values such as gender were administered. Data including age, gender and symptoms were also collected [4].…”
Section: Sample Collectionmentioning
confidence: 99%
“…The findings of this study shown low percentage of the Staphylococcus and Pseudomonas [4] species in the ear and throat of patients as points to the high level of frequent and indescrimate use of antibiotics which in turn resulted to high level of resistant of common uses antibiotics such as Augmentin, Gentamicin, Erythromycin and Ceftazidime among patient suffering from symptoms of ENT resulting to difficulty in the treatment of infections using the common [5] .…”
Section: Conclusion and Recommenda-tionsmentioning
confidence: 99%
See 2 more Smart Citations